Organic Stereochemistry. Part 21. Issue 2 (18th February 2013) - Testa, Bernard
Abstract This review continues a general presentation of the principles of stereochemistry with special reference to medicinal compounds. Here, we explore stereoisomeric compounds characterized by a single or several stereogenic centers (often also called centers of chirality). The main focus will be on chiral tetrahedral structures, namely a) tetracoordinate centers, and b) tricoordinate centers where an electron lone pair plays the role of the fourth substituent, forming a tetrahedron. Following an overview of the main tetrahedral structures of interest in biological and medicinal stereochemistry, the review places emphasis on explaining the two dominant conventions, namely the d, l‐ and (R, S)‐convention, the latter being known as the CIP (CahnIngoldPrelog) convention. The review ends with a discussion of reactions of stereoisomerization at stereogenic C‐centers and its relevance to drug research.